Revisiting reef models in the Oligocene of northern Italy (Venetian Southern Alps) - Bosellini, Francesca R.; Vescogni, Alessandro; Kießling, Wolfgang; Zoboli, Alessandro; Di Giuseppe, Dario; Papazzoni, Cesare Andrea (Bollettino Della Societa Paleontologica Italiana, 2020)
The lower Oligocene coral communities and reefs exposed in the Lessini Shelf of northern Italy may record one of the oldest well-developed barrier reef/lagoon systems of the Cenozoic. However, the rimmed-shelf interpretation has been repeatedly challenged in favour of a ramp model with scattered corals. Based upon a re-analysis of selected localities in the Lessini Shelf, we here provide support for the barrier reef model based on four key observations: 1) systematic changes of coral growth-forms from branching in the proximal areas to massive at the platform margin; 2) a progressive increase of the hydrodynamic energy from the proximal belt towards the more distal environments in the Berici Hills; 3) the occurrence of shallow-water, euphotic conditions throughout the whole depositional system; and 4) the presence of restricted circulation in the proximal environments during sea-level lowstands, with lack of coral colonies. These features, together with the evidence of coral frameworks located on the southeastern edge of the Lessini Shelf, substantiate the occurrence of a reef-rimmed margin. The reefal rim acted as an efficient barrier, with the formation of a landward, wide lagoon protected from the action of waves and currents.
CRIS-Team WoS Importer:2021-01-29